Granulocyte-Derived Extracellular Vesicles Activate Monocytes and Are Associated With Mortality in Intensive Care Unit Patients - Danesh, Ali; Inglis, Heather C.; Abdel-Mohsen, Mohamed; Deng, Xutao; Adelman, Avril; Schechtman, Kenneth B.; Heitman, John W.; Vilardi, Ryan; Shah, Avani; Keating, Sheila M.; Cohen, Mitchell J.; Jacobs, Evan S.; et al. (Frontiers in Immunology, 2018)
To understand how extracellular vesicle (EV) subtypes differentially activate monocytes, a series of in vitro studies were performed. We found that plasma-EVs biased monocytes toward an M1 profile. Culturing monocytes with granulocyte-, monocyte- and endothelial-EVs induced several pro-inflammatory cytokines. In contrast, platelet-EVs induced TGF-β and GM-CSF, and red blood cell (RBC)-EVs did not activate monocytes in vitro. The scavenger receptor CD36 was important for binding of RBC-EVs to monocytes, while blockade of CD36, CD163, CD206, TLR1, TLR2, and TLR4 did not affect binding of plasma-EVs to monocytes in vitro. To identify mortality risk factors, multiple soluble factors and EV subtypes were measured in patients’ plasma at intensive care unit (ICU) admission. Of 43 coagulation factors and cytokines measured, two were significantly associated with mortality, TPA and cystatin C. Of 14 cellular markers quantified on EVs, 4 were early predictors of mortality, including the granulocyte marker CD66b. In conclusion, granulocyte-EVs have potent pro-inflammatory effects on monocytes in vitro. Furthermore, correlation of early granulocyte EV levels with mortality in critically ill patients provides a potential target for intervention in management of the pro-inflammatory cascade associated with critical illness.